Differences in Vestibular-Evoked Myogenic Potential Responses by Using Cochlear Implant and Otolith Organ Direct Stimulation - Rodriguez Montesdeoca, Isaura; Ramos de Miguel, Angel; González, Juan Carlos Falcon; Barreiro, Silvia Borkoski; Pérez Fernández, Nicolás; Vanspauwen, Robby; Ramos-Macias, Angel (Frontiers in Neurology, 2021)
Objective: Several studies have demonstrated the possibility to obtain vestibular potentials elicited with electrical stimulation from cochlear and vestibular implants. The objective of this study is to analyze the vestibular-evoked myogenic potentials (VEMPs) obtained from patients implanted with cochlear and vestibulo-cochlear implant. Material and Methods: We compared two groups: in the first group, four cochlear implant (CI) recipients with present acoustic cVEMPs before CI surgery were included. In the second group, three patients with bilaterally absent cVEMPs and bilateral vestibular dysfunction were selected. The latter group received a unilateral cochleo-vestibular implant. We analyze the electrically elicited cVEMPs in all patients after stimulation with cochlear and vestibular electrode array stimulation. Results: We present the results obtained post-operatively in both groups. All patients (100%) with direct electrical vestibular stimulation via the vestibular electrode array had present cVEMPs. The P1 and N1 latencies were 11.33–13.6 ms and 18.3–21 ms, respectively. In CI patients, electrical cVEMPs were present only in one of the four subjects (25%) with cochlear implant (“cross”) stimulation, and P1 and N1 latencies were 9.67 and 16.33, respectively. In these patients, the responses present shorter latencies than those observed acoustically. Conclusions: Electrically evoked cVEMPs can be present after cochlear and vestibular stimulation and suggest stimulation of vestibular elements, although clinical effect must be further studied.